Comparison of Diagnostic Accuracy of 2 Cone Beam Computed Tomography System (Newtom &Planmeca) for Detection of External Root Resorption in Vitro - Marjan Bolbolian; Mahsa Esfehan; Neda Hajihassani; Zohreh Khalili; Mahshid Mobini; Maryam Tofangchiha (Isfahan University of Medical Sciences, 2022)
External root resorption is a clinical problem that is difficult to diagnose, therefore radiographic examination is important for diagnose. The purpose of this study was comparing the diagnostic accuracy of 2 Cone Beam Computed Tomography in detecting of external root resorption, in vitro.Materials & Methods:This study was done on 48 single-rooted teeth. Cavities of 0.3, 0.2 and 0.15 mm in depth with round bur 0.3 mm were drilled on buccal and lingual surfaces in the cervical, middle and apical thirds of some of roots. Then CBCT were taken and 4 observers assessed the scans. Sensitivity, specificity and Kappa value were determined. The statistical analysis was performed with the Z-test (p value < 0.05).Results:In comparison of the accuracy, sensitivity and specificity of the two devices, there was no significant difference. In the apical, middle and cervical as well as at various depths there was no significant difference between the two devices, but in the numerical point of view, the sensitivity for both devices in the midsection, was in the highest amount. The highest value for the specificity is related to the apical region. For both devices, the sensitivity level GBJ, by increasing the depth. The lowest agreement between observers was 0.61. The highest agreement rate was in the middle section and the least amount of agreement was related to the apical region.Conclusion:CBCT brand type is not effective factor in the detection of external root resorption. The location and depth of external root resorption can be effective factors in diagnostic accuracy